Micro-Raman analysis of Ba0.2Sr0.8TiO3 (barium strontium titanate) doped of chlorophyll of cassava leaf. (17th February 2019) - Palupi, Endah Kinarya; Umam, Rofiqul; Andriana, Bibin Bintang; Sato, Hidetoshi; Yuliarto, Brian; Alatas, Husin; Irzaman
Abstract: This paper informs how the optical and crystalline properties of Barium Strontium Titanate film are treated with chlorophyll of cassava leaves. Chlorophyll is extracted from cassava leaves and then processed into powder that is ready to be used as a dopant. Ba0.2 Sr0.8 TiO3 film doped of chlorophyll was fabricated on a p-type silicon substrate using chemical solution deposition method with a spin coating technique. The degree of crystallinity of films is also studied using X-Ray Diffractometer. Also, this sample was analysed using Micro-Raman Spectroscopy. With this analysis, a performance description of the Ba0.2 Sr0.8 TiO3 thin film is obtained by chlorophyll of cassava leaves which is expected to become one of the reliable electronic device components in the future.